Smart Planning: Sustainability and Mobility in the Age of Change (Green Energy and Technology,, 2018)
This book offers an overview of sustainability and urban mobility in the context of urban planning - topics that are of considerable interest in the development of smart cities. Environmental sustainability is universally recognized as a fundamental condition for any urban policy or urban management activity, while mobility is essential for the survival of complex urban systems. The new opportunities offered by innovations in the mobility of people, goods and information, as well as radically changing interactions and activities are transforming cities. Including contributions by urban planning scholars, the book provides an up-to-date picture of the latest studies and innovative policies and practices in Italy, of particular interest due to its spatial, functional and social peculiarities. Sustainability and mobility must form the basis of "smart planning" - a new dimension of urban planning linked to two main innovations: procedural innovation in the management of territorial transformations and the technological innovation of the generation, processing and distribution of data (big data) for the creation of new "digital environments" such as GIS, BIM, models of augmented and mixed reality, useful for describing changes in human settlement in real time.